Implementation Of Religious Speech Activity Program In Forming Leadership Character In Grade VIII At MTsN 1 Karanganyar In The 2023/2024 Academic Year - Rahmahdani, Ghaitsa Shofa (Yayasan Rahmat Islamiyah, 2025)
This study aims to determine the implementation and supporting and inhibiting factors of the religious speech activity program in forming leadership character in class VIII students at MTs Negeri 1 Karanganyar in the 2023/2024 Academic Year. This study uses a qualitative method with a field research. The results of this study indicate that in organizing a religious lecture program there are 3 stages, namely planning, implementation, and evaluation. Supporting factors are 1) Availability of supporting facilities and infrastructure, 2) The language used in the religious lecture program is not only Indonesian, and 3) Support from parties involved in the religious lecture program. While the inhibiting factors are 1) Student factors, namely students are difficult to manage, not confident, and others, 2) Teacher factors, namely some homeroom teachers and language subject teachers pay less attention to their students in this program and lack of communication between teachers, 3) Language barriers, namely students do not necessarily understand the contents of religious lectures delivered in different languages. From this activity program, attitudes of self-confidence, responsibility, discipline, and care are also formed which describe a leader from his leadership character.